Intergenerational conflict or solidarity between the young and the old? The Austrian long-term care system in a European comparison - Schmidt, Andrea E. (Momentum Quarterly, 2014)
This paper analyses the design of the Austrian long-term care system for older people from a perspective of intergenerational solidarity, and in comparison with other European countries. In particular, the analysis focuses on the structures underlying the financing, provision and governance of the long-term care system, also in comparison with social policies in the field of family benefits and child care. It is shown that Austria has a relatively generous system of public support for older people by international standards, which is mainly based on cash benefits. This is also true for long-term care, where a large number of dependent older people are reached, while the amount of the benefits is relatively small. Long-term care benefits are financed from general taxes, as well as user co-payments, which means that funding is based mainly on taxation of income from paid work. Large differences are found in the financial and actual responsibility attributed to families – and especially younger generations – in securing care for their dependent relatives across Austria’s federal states, due to highly varying regulations regarding co-payments and obligation for family members to contribute to the costs of care. It follows that the introduction of ‘long-term care taxes’ on assets could contribute to a better balance of the elements of the system under aspects of solidarity, including but not limited to intergenerational solidarity. A national extension of long-term care services, as well as a harmonization of regulations regarding private co-payments represent a precondition for being able to judge solidarity between generations regardless of one’s social class and one’s place of residence.